2014
DOI: 10.1186/1756-0500-7-122
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric predictors of gestational hypertensive disorders in a remote aboriginal community: a nested case–control study

Abstract: BackgroundAustralian Aboriginal women tend to have body shape and pregnancy risk profiles different from other Australian women. This study aims to examine the associations of anthropometric indices with gestational hypertensive disorders (GHD), and to determine the index that can best predict the risk of this condition occurring during pregnancy.MethodsThis is a nested case–control study. Baseline body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR) and waist-to-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The study proved that the gestational age, pregestational BMI and RDW at 20th week of pregnancy were the high risk factors of the PHD by the Logistic regression analysis. Age and BMI as high risk factors of the PHD was in line with the existing reports . But RDW as a new PHD risk factor has not been reported.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study proved that the gestational age, pregestational BMI and RDW at 20th week of pregnancy were the high risk factors of the PHD by the Logistic regression analysis. Age and BMI as high risk factors of the PHD was in line with the existing reports . But RDW as a new PHD risk factor has not been reported.…”
Section: Discussionsupporting
confidence: 85%
“…Age and BMI as high risk factors of the PHD was in line with the existing reports. [9][10][11][12][13] But RDW as a new PHD risk factor has not been reported. Only reported that the relationship between RDW and preeclampsia, and there were obvious disputes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, BMI, as well as waist circumference were statistically significant in predicting the development of hypertension in pregnancy. 12 However, this study had smaller participant numbers (n = 28) in a rural setting and did not explore any other risk factors for HDP. The only other published Australian study that examined risk factors for hypertension in pregnancy in ATSI women was published in 1996.…”
Section: Discussionmentioning
confidence: 93%
“…Several hypotheses were suggested for the higher than national BMI reported in this study, such as the lack of availability of healthy foods and safe environments in which to exercise . A nested case control study from the Northern Territory, again examined the predictive effect of anthropometric measurements in the Aboriginal community . Similarly, BMI, as well as waist circumference were statistically significant in predicting the development of hypertension in pregnancy .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation